Digitalisasi Pelayanan Pertanahan: Studi Efektivitas Pendaftaran Tanah Online di Kabupaten Kendal - ela kurniasari (CV Rewang Rencang, 2025)
This study aims to measure the effectiveness of post-online land registration services at the Kendal District Land Office, which is part of the modernization of digital-based public services. The research method used is qualitative with an empirical juridical approach through interviews, observations, and document studies. The results of the study show that the implementation of the Sentuh Tanahku system has not been optimal, as indicated by the long queues of people. The inhibiting factors include technical system disruptions, limited human resource competencies, and the incompatibility of land data with the digital system. Therefore, it is necessary to increase human resource capacity, improve the system, and educate the public to realize effective, accountable, and sustainable land services.